PENGEMBANGAN MEDIA GUIDE WRITING BERBASIS MENJIPLAK UNTUK MENINGKATKAN KEMAMPUAN MENULIS HURUF VOKAL PADA ANAK USIA 4-5 TAHUN DI TK KHADIJAH 99 TEGALARUM SEMPU BANYUWANGI TAHUN AJARAN 2022/2023 - Astutik, Puji; Syamsudin, Moh. Anas; Haris Fauzi, Alex (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2023)
Based on observations made on children aged 4-5 years in Khadijah Tegalyasan Kindergarten, Tegalarum Village, Sempu District, obtained data that the ability to write vowels in children has not developed properly optimal. This requires handling steps so that the ability of students in Khadijah Tegalyasan Kindergarten, Tegalarum Village, Sempu District can develop. An alternative handling in this study is to create media in the form of guide writing media based on tracing. This study aims to (1) know the steps for developing guide writing media based on tracing in improving the ability to write vowels in children aged 4-5 years, (2) find out the feasibility of guide writing media based on tracing for children aged 4-5 years. This development research uses the Borg and Gall model by taking 8 development steps. Data collection techniques in this study are observation, interviews, questionnaires and documentation. Data analysis techniques use the Likert scale by calculating the average of the number of values obtained. The subjects involved in this study were 1 material and media expert, 1 class teacher and 28 students. The results of this study are as follows, (1) the Borg and Gall development model used only takes 8 development steps. The media is made in the form of a guide board that contains material or letter symbols as a guide and learning guide for children. (2) The media was tested to be effective for improving the writing skills of children aged 4-5 years through operational tests by comparing the results of scores obtained by children at the first to last meeting with an average score of 3.5.